2023
DOI: 10.1177/03635465221148746
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Outcomes of Revision and Primary ACL Reconstruction: A Matched-Pair Analysis With 3-5 Years of Follow-up

Abstract: Background: There are limited studies designed by matching related factors to compare clinical outcomes and return to sport (RTS) between patients undergoing revision anterior cruciate ligament reconstruction (R-ACLR) and primary ACLR (P-ACLR). Purpose: (1) To compare the outcomes between R-ACLR and P-ACLR in a matched-pair analysis with 3- to 5-year follow-up and (2) to evaluate patient-reported factors for not returning to preinjury-level sport. Study Design: Cohort study; Level of evidence, 4. Methods: Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…However, the same meta-analysis [ 10 ] reported that there were insufficient data of patient-reported scores other than the Lysholm score, such as the IKDC-SKF or the KOOS. In contrast, a previous matched-group analysis based on 63 patients with revision ACLR and primary ACLR was not able to find significant differences in the Lysholm score between the groups at 3 to 5 years of follow-up [ 13 ]. A clinical review from 2019 [ 11 ] concluded that patients with revision ACLR have poorer patient-reported outcomes, but most studies evaluating patient-reported outcomes comparing revision and primary ACLR have small patient samples, a short follow-up and are mostly retrospective.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, the same meta-analysis [ 10 ] reported that there were insufficient data of patient-reported scores other than the Lysholm score, such as the IKDC-SKF or the KOOS. In contrast, a previous matched-group analysis based on 63 patients with revision ACLR and primary ACLR was not able to find significant differences in the Lysholm score between the groups at 3 to 5 years of follow-up [ 13 ]. A clinical review from 2019 [ 11 ] concluded that patients with revision ACLR have poorer patient-reported outcomes, but most studies evaluating patient-reported outcomes comparing revision and primary ACLR have small patient samples, a short follow-up and are mostly retrospective.…”
Section: Discussionmentioning
confidence: 89%
“…A previous study comparing patients with revision ACLR and primary ACLR regarding RTS at nine months after surgery reported that athletes with primary ACLR were more likely to have returned to sport [ 31 ]. Another study, comparing athletes with revision ACLR with matched athletes with primary ACLR, reported that athletes with primary ACLR were more likely to RTS overall (84% vs 65%), but there were no differences between the groups regarding the return to the same activity level (56% vs 49%) 3 to 5 years of follow-up [ 13 ]. In our study, the main reasons for not RTS were fear of re-injury in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…R-ACLRs tend to result in worse outcomes than that of primary operations [5,6]. As such, technical aspects of r-ACLR have been studied extensively in the adult literature over the past several years, including optimal graft selection, tunnelling and fixation strategies, and staging [7][8][9].…”
Section: Introductionmentioning
confidence: 99%